PENGARUH PENGGUNAAN PASIR BALIKPAPAN TERHADAP KEKERASAN DAN FLUIDITAS LOGAM CORAN PADUAN Al-Si - Sabdha Purna Yudha (Otopro, 2021)
The use of sand as a mold in the casting process is very common. In this study, Balikpapan sand used as casting sand then analyzed its effect on hardness and fluidity of the Al-Si alloy. The research method used in this research is quantitative research methods using pre-experimental design, especially the one-shot case study model. The final results of this study will be obtained (1) the value of metal hardness from casting using the Micro Vickers Hardness Tester with a Hardness Vickers (HV) scale, (2) fluidity testing is carried out using the Birmingham method in order to determine the length of the cast metal flow (mm) on the final result of casting.